Genomic characterisation of Arachis porphyrocalyx (Valls & C.E. Simpson, 2005) (Leguminosae): Multiple origin of Arachis species with x = 9 - Silvestri, María Celeste (2017)
The genus Arachis Linnaeus, 1753 comprises four species with x = 9, three belong to the section Arachis: Arachis praecox (Krapov. W.C. Greg. & Valls, 1994), Arachis palustris (Krapov. W.C. Greg. & Valls, 1994) and Arachis decora (Krapov. W.C. Greg. & Valls, 1994) and only one belongs to the section Erectoides: Arachis porphyrocalyx (Valls & C.E. Simpson, 2005). Recently, the x = 9 species of section Arachis have been assigned to G genome, the latest described so far. The genomic relationship of A. porphyrocalyx with these species is controversial. In the present work, we carried out a karyotypic characterisation of A. porphyrocalyx to evaluate its genomic structure and analyse the origin of all x = 9 Arachis species. Arachis porphyrocalyx showed a karyotype formula of 14m+4st, one pair of A chromosomes, satellited chromosomes type 8, one pair of 45S rDNA sites in the SAT chromosomes, one pair of 5S rDNA sites and pericentromeric C-DAPI+ bands in all chromosomes. Karyotype structure indicates that A. porphyrocalyx does not share the same genome type with the other three x = 9 species and neither with the remaining Erectoides species. Taking into account the geographic distribution, morphological and cytogenetic features, the origin of species with x = 9 of the genus Arachis cannot be unique; instead, they originated at least twice in the evolutionary history of the genus.